Pengaruh Likuiditas, Leverage, Firm Size Dan Profitabilitas Terhadap Nilai Perusahaaan Food And Beverage Yang Terdaftar Di BEI Priode 2017-2020 - Septina Fenny Kok; Lasma Ria Tampubolon; William William; Denisse Yinarta; Steven Richard; Ezzah Nahrisah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of the study was to test and analyze the effect of liquidity, leverage, firm size and profitability on the value of food and beverage companies listed on the IDX for the period 2017-2020. The population used in this study is a company listed food and beverage index on the Indonesia Stock Exchange in the period 2017-2020 which amounted to 38 companies, a sample of 26 companies and a total of 104 observations. The sampling technique used is purposive Sampling. The results of partial hypothesis testing that Leverage and liquidity have a negative and significant effect on the value of food and beverage companies listed on the IDX for the period 2017-2020. the results of simultaneous hypothesis testing that liquidity, leverage, firm size and profitability have a positive and significant effect on the value of food and beverage companies listed on the IDX for the period 2017-2020. Keywords: Liquidity, Leverage, Firm Size, Profitability, Company Value